2023
DOI: 10.1159/000529242
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic Risk Factors in Atorvastatin-Treated Women with Euthyroid Autoimmune Thyroiditis

Abstract: <b><i>Introduction:</i></b> Autoimmune thyroiditis seems to be associated with increased cardiometabolic risk. Statins, the mainstay of cardiovascular risk reduction and prevention, were found to reduce thyroid antibody titers. The aim of this study was to investigate plasma markers of cardiometabolic risk in statin-treated women with thyroid autoimmunity. <b><i>Methods:</i></b> We compared two matched groups of euthyroid women with hypercholesterolemia receiving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…Metformin-induced reduction in thyrotropin levels was observed in women with subclinical hypothyroidism of both autoimmune and nonautoimmune origin coexisting with polycystic ovary syndrome and did not depend on titers of thyroid antibodies [19]. However, recently, the same research group has reported that women with Hashimoto's thyroiditis were partially resistant to the cardiometabolic effects of atorvastatin [20]. Therefore, the current study was aimed at investigating whether thyroid autoimmunity modulates the impact of metformin on circulating levels of prolactin, other anterior pituitary hormones and their downstream hormones in young women with prolactin excess.…”
Section: Introductionmentioning
confidence: 97%
“…Metformin-induced reduction in thyrotropin levels was observed in women with subclinical hypothyroidism of both autoimmune and nonautoimmune origin coexisting with polycystic ovary syndrome and did not depend on titers of thyroid antibodies [19]. However, recently, the same research group has reported that women with Hashimoto's thyroiditis were partially resistant to the cardiometabolic effects of atorvastatin [20]. Therefore, the current study was aimed at investigating whether thyroid autoimmunity modulates the impact of metformin on circulating levels of prolactin, other anterior pituitary hormones and their downstream hormones in young women with prolactin excess.…”
Section: Introductionmentioning
confidence: 97%
“…Women with hypercholesterolemia with Hashimoto thyroiditis have recently been found resistant to cardiometabolic effects of atorvastatin. 20 The paucity of data encouraged us to investigate whether autoimmune thyroiditis determines cardiometabolic effects of cabergoline in young women with hyperprolactinemia.…”
mentioning
confidence: 99%
“…Prolactin excess and autoimmune thyroiditis may coexist with each other, particularly in women of reproductive age, and such patients may be more susceptible to the development of cardiovascular and metabolic disorders than individuals with isolated hyperprolactinemia or isolated autoimmune thyroid disease. Women with hypercholesterolemia with Hashimoto thyroiditis have recently been found resistant to cardiometabolic effects of atorvastatin 20 . The paucity of data encouraged us to investigate whether autoimmune thyroiditis determines cardiometabolic effects of cabergoline in young women with hyperprolactinemia.…”
mentioning
confidence: 99%